Study of reasons for enterprise systems adoption among Indian organizations. Issue 6 (23rd August 2014) - Ahmad, Naim; Haleem, Abid; Syed, Asif Ali
Abstract : Purpose: The purpose of this paper is to identify reasons for the Enterprise Systems adoption, their relevance to the Indian organizations and their relationship with industry and size among the Indian Organizations. Design/methodology/approach: Through the content analysis of twelve research papers reasons of Enterprise Systems adoption have been identified. With the resultant framework of variables, 288 Indian cases have been scanned to identify and contrast adoption reasons in India with other countries. Also through chi-square test their associations have been studied with respect to industry and size among Indian Organizations. Findings: All the adoption reasons are present in Indian Organizations. All the adoption reasons are indifferent to the industry of organization. Similarly it is found that all the adoption reasons but one is indifferent to the size of organization. Only Organizational Change is found to be significantly related with the size. Research limitations/implications: The scope of study is limited to the Indian organizations that have implemented Enterprise Systems software. All the manifest variables have been marked with only two values 0 for absence and 1 for presence while omitting the information on relative strength. There is potential possibility of bias towards ES implementation benefits and relative comfort in implementing the target vendor's product. This research has utilized secondary data that might not have been created to address the current problem therefore may be limited in relevancy and accuracy. Practical implications: Adoption motivations are a good starting point to see the need for the ES. Occurrences of adoption motivations advocate the change in the Application infrastructure. Following 12 motivations for the adoption of ES have been identified in the literature review. Moreover they haven't varied much with respect to the size and industry of the organizations. However some factors are showing stronger presence in Indian context than the global counterparts and some are showing weaker presence. Originality/value: Content analysis of the literature review has resulted in twelve reasons for the Enterprise Systems adoption after three iterations. These variables have been explained with the help of literature. Second component of this research studies the relationship of these variables with Industry and size among Indian organizations. It is established that Enterprise Systems are being adopted globally for the identical reasons. These reasons are also almost uniform with respect to industry and size of the Indian organizations.